2016
DOI: 10.1038/srep36416
|View full text |Cite|
|
Sign up to set email alerts
|

AGEs Induced Autophagy Impairs Cutaneous Wound Healing via Stimulating Macrophage Polarization to M1 in Diabetes

Abstract: Autophagy is essential in physiological and pathological processes, however, the role of autophagy in cutaneous wound healing and the underlying molecular mechanism remain elusive. We hypothesized that autophagy plays an important role in regulating wound healing. Here, we show that enhanced autophagy negatively impacts on normal cutaneous healing process and is related to chronic wounds as demonstrated by the increased LC3 in diabetic mice skin or patients’ chronic wounds. In addition, inhibition of autophagy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 41 publications
(49 reference statements)
7
82
0
Order By: Relevance
“…To observe the effects of AFB 1 on the polarization of SIV-infected PAMs, PAMs were seeded on coverslips and infected with SIV for 24 h. Subsequently, groups of cells were further exposed to polarizing cytokines and AFB 1 for an additional 24 h, as follows: Group 1 (M1 control): LPS (100 ng/ml) plus IFN-γ (25 ng/ ml); Group 2 (M2 control): IL-4 (25 ng/ml) [30][31][32]; Group 3: AFB 1 (0 µg/ml); Group 4: AFB 1 (0.02 µg/ml); and Group 5: AFB 1 (0.04 µg/ml). At the end of the incubation period, PAMs were washed three times with PBS and were then fixed in 2.5% glutaraldehyde for 4 h at 4°C.…”
Section: Observation Of Pam Polarization By Scanning Electron Microscopymentioning
confidence: 99%
“…To observe the effects of AFB 1 on the polarization of SIV-infected PAMs, PAMs were seeded on coverslips and infected with SIV for 24 h. Subsequently, groups of cells were further exposed to polarizing cytokines and AFB 1 for an additional 24 h, as follows: Group 1 (M1 control): LPS (100 ng/ml) plus IFN-γ (25 ng/ ml); Group 2 (M2 control): IL-4 (25 ng/ml) [30][31][32]; Group 3: AFB 1 (0 µg/ml); Group 4: AFB 1 (0.02 µg/ml); and Group 5: AFB 1 (0.04 µg/ml). At the end of the incubation period, PAMs were washed three times with PBS and were then fixed in 2.5% glutaraldehyde for 4 h at 4°C.…”
Section: Observation Of Pam Polarization By Scanning Electron Microscopymentioning
confidence: 99%
“…IRF8 has been characterized, in previous research, to be a central element and functions downstream of the IFN-γ signaling pathway that involves IFN-γ's binding to the receptor STAT1 and is recognized to regulate the activation of the proin ammatory M1 phenotype macrophages [22]. Consistently, IRF8 activation was also proved to induce M1 polarization of macrophages after advanced glycation endproducts treatment previously [23]. Moreover, IRF8 could be controlled by the Notch-RBP-J signaling pathway to participate in the regulation of TLR-induced in ammatory polarization of macrophages, namely the M1 macrophages polarization [24].…”
Section: Discussionmentioning
confidence: 78%
“…Autophagy also plays a role in oxidative injury . AGE‐induced autophagy has been linked to impaired cutaneous wound healing through stimulation of the M1 polarized macrophage . M1 macrophages promote inflammation, and prolonged inflammation has been noted in delayed wound healing.…”
Section: Wound Healingmentioning
confidence: 99%
“…M1 macrophages promote inflammation, and prolonged inflammation has been noted in delayed wound healing. Additionally, Guo and colleagues reported that in the presence of AGEs, the autophagy regulator IRF8 is upregulated, suggesting that in diabetes autophagy is excessive and linked to delayed wound healing.…”
Section: Wound Healingmentioning
confidence: 99%